Aromatic Nanosandwich Obtained by σ-Dimerization of a Nanographenoid π-Radical - Moshniaha, Liliia; Żyła-Karwowska, Marika; Chmielewski, Piotr J.; Lis, Tadeusz; Cybińska, Joanna; Gońka, Elżbieta; Oschwald, Johannes; Drewello, Thomas; Rivero, Samara Medina; Casado, Juan; Stȩpień, Marcin (Journal of the American Chemical Society, 2020)
A 139-π-electron nanographenoid radical was obtained by expanding the periphery of a naphthalimide-azacoronene hybrid with a methine bridge. The radical was isolated in the form of its σ-dimer, which was shown to possess a conformationally restricted two-layer structure both in the solid state and in solution. The dimer is cleaved into its parent radicals when exposed to ultraviolet or visible radiation in toluene solutions but is resistant to thermally induced dissociation. Under inert conditions, the radicals recombine quantitatively into the σ-dimer with observable kinetics, but they are oxidized into a ketone derivative in the presence of atmospheric oxygen. Combined structural, spectroscopic, and theoretical evidence shows that the σ-dimer contains a weak C(sp3)-C(sp3) bond, but is stabilized against thermal dissociation by a very strong dispersive interaction between the overlapping πsurfaces.
CRIS-Team Scopus Importer:2020-03-10